HUBUNGAN PENGETAHUAN GIZI IBU HAMIL TRIMESTER II DAN III TERHADAP PENINGKATAN BERAT BADAN SELAMA KEHAMILAN DI PUSKESMAS KAMPUS PALEMBANG TAHUN 2022 - hanik khairun nisa (UNIVERSITAS HAJI SUMATERA UTARA, 2023)
Fulfillment of nutrition for pregnant women is important because it will have an impact on both the mother and the baby she is carrying. Pregnant women who have poor nutritional status can pose a risk to the growth and development of their fetus, babies with birth defects, low birth weight (LBW) can even cause infant death in the womb. The achievement of nutritional needs during pregnancy is one of which is influenced by maternal knowledge related to nutrition during pregnancy. The research design used in this study was analytic with a cross-sectional approach using primary data by measuring the knowledge of pregnant women using a questionnaire while assessing the increase in body weight was seen from the KIA/KMS book. Sampling was carried out at the Puskesmas Kampus Palembang. The sample used in this study was 40 people who met the inclusive criteria. Data analysis used Chi Square with α=0.05 and CI=95%. The results of this study are that there is a relationship between nutritional knowledge in pregnant women and weight gain during pregnancy at the Puskesmas Kampus Palembang with a p-value = 0.002. From the results of this study it can be interpreted that nutritional knowledge in pregnant women affects weight gain during pregnancy.